Mechanical characterization and environmental assessment of stabilized earth blocks. Issue 1 (1st December 2022) - Arairo, W; Saba, M; Bachawati, M El; Absi, J; Kontoleon, K J
Abstract: Soil is a local material which allows populations in warm regions to better cope with severe environmental conditions. The materials' performance depends on the chemical and physical nature of the soil. The greatest problem with these materials remains their high sensitivity to shrinkage, and their vulnerability in terms of cracking due to drying. These pathologies may lead to a radical decrease in their mechanical performance. Several works have indicated that the consideration of plant fibers, as reinforcement in earth materials, made it possible to avoid cracking, and, thus, ensure the stability of structures. These results are not generalizable and depend on the involved materials. This work aims to investigate different scenarios for the stabilization of earth blocks. In this context, the use of cement with two types of natural fibers for the stabilization of Lebanese earth blocks has been studied. The mechanical properties of stabilized earth blocks have shown that the developed mix provides suitable results compared to the traditional masonry block. The environmental impacts of earth blocks have been compared using SimaPro software. The results of this study show that the stabilized earth blocks are gaining their place as a sustainable, affordable building material suitable for low-cost construction.